2001
DOI: 10.2176/nmc.41.565
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Neurosurgical Navigational System for Transsphenoidal Surgery. Technical Note.

Abstract: Transsphenoidal surgery carries the risk of carotid artery injury even for very experienced neurosurgeons. The computer-assisted neurosurgical (CANS) navigational system was used to obtain more precise guidance, based on the axial and coronal images during the transsphenoidal approach for nine pituitary adenomas. The CANS navigator consists of a three-dimensional digitizer, a computer, and a graphic unit, which utilizes electromagnetic coupling technology to detect the spatial position of a suction tube attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A deviation of 3 mm within the sella is too great to allow the surgeon to be guided by the Viewscope alone, and thus the results of this comparison suggest that such stereotactic devices should remain supplemental to fluoroscopy and to the surgeon's understanding of the anatomy involved. Onizuka et al [31] reported that stereotactic guidance was of little value to experienced surgeons skilled in pituitary procedures, but that these systems were of great value to younger neurosurgeons. In our hands, the combination of the Viewscope and fluoroscope provides optimal information for a successful outcome in transsphenoidal surgery.…”
Section: Specific Experiences With the Viewscopementioning
confidence: 99%
“…A deviation of 3 mm within the sella is too great to allow the surgeon to be guided by the Viewscope alone, and thus the results of this comparison suggest that such stereotactic devices should remain supplemental to fluoroscopy and to the surgeon's understanding of the anatomy involved. Onizuka et al [31] reported that stereotactic guidance was of little value to experienced surgeons skilled in pituitary procedures, but that these systems were of great value to younger neurosurgeons. In our hands, the combination of the Viewscope and fluoroscope provides optimal information for a successful outcome in transsphenoidal surgery.…”
Section: Specific Experiences With the Viewscopementioning
confidence: 99%
“…There are still some limitations for conventional neuronavigation, in which the guidance provided for 3-dimensional orientation of the sellar region and the assessment of the extent of tumor resection, are primarily based on preoperative imaging datasets. The morphological and structural deformations of the tumor lesion and perisellar soft tissues that occurred during the tumor removal cannot be accounted for, which definitely influence the accuracy and safety of surgical guidance (26). To address this shortcoming, real-time intraoperative imaging technology is necessary.…”
mentioning
confidence: 99%
“…CT-based frameless stereotactic navigation has been routinely used in cranial and spinal neurosurgical procedures for over 25 years and has been successfully applied to TSS [3,32,33,45,[50][51][52][53][54][55][56]. The benefits of CTbased navigation include low cost, short acquisition time, and excellent detail of sinus and bony anatomy.…”
Section: Navigation Technologymentioning
confidence: 99%
“…Multiple reports describe the use of this modality in TSS [3,40,41,53,54,[56][57][58][59]. Registration of the system may be rapidly accomplished using either implanted fiducial markers or surface registration.…”
Section: Navigation Technologymentioning
confidence: 99%